Preservation of meaning in mosque architecture using Heritage Building Information Modeling (HBIM): a case study of the iconic Al-Hilal Katangka Mosque, Gowa, South Sulawesi, Indonesia - Sutrisno, Moh.; Syafar, A. Muhammad (2024)
This research aims to document the meanings of building elements in digital applications. Building Information Modeling (BIM) helps researchers and architects collect information on the meanings and values of old building elements in 3-dimensional models. The architectural elements of the Al-Hilal Katangka Gowa Mosque are the characteristics that reinforce the historical significance and pride of the Gowa district. However, the meanings and values are not integrated into a single object. On the other hand, mosque buildings have the potential to be maintained with the HBIM digital platform. This research uses a content analysis method with a rationalistic paradigm. The research results show that every meaning and value can be understood when accessed through a three-dimensional model. Augmented reality projects 2D and 3D virtual models that can be interactively and effectively projected in real time. ArchiCAD software is used to collect the meanings of roofs, walls and columns into a single 3-dimensional model.